2017
DOI: 10.1093/hmg/ddx153
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygote galactocerebrosidase (GALC) mutants have reduced remyelination and impaired myelin debris clearance following demyelinating injury

Abstract: Genome-wide association studies are identifying multiple genetic risk factors for several diseases, but the functional role of these changes remains mostly unknown. Variants in the galactocerebrosidase (GALC) gene, for example, were identified as a risk factor for Multiple Sclerosis (MS); however, the potential biological relevance of GALC variants to MS remains elusive. We found that heterozygote GALC mutant mice have reduced myelin debris clearance and diminished remyelination after a demyelinating insult. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 78 publications
6
15
0
Order By: Relevance
“…In our study, upregulation of TREM2 expression could be observed in both models of axonal injury, being coincident with the previous general in vivo data in chronic (Jay et al, 2017a;Sayed et al, 2018) and acute CNS inflammatory injuries (Saber et al, 2017;Scott-Hewitt et al, 2017;Wu et al, 2017), as well as in other axonal injury models (Kobayashi et al, 2016;Tay et al, 2018). Additionally, an increase in sTREM2 could be found at the peak of TREM2 microglial expression after PPT, which was not detected after FNA.…”
Section: Trem2 Is Increased In Activated Microglial Cells After Both supporting
confidence: 91%
See 1 more Smart Citation
“…In our study, upregulation of TREM2 expression could be observed in both models of axonal injury, being coincident with the previous general in vivo data in chronic (Jay et al, 2017a;Sayed et al, 2018) and acute CNS inflammatory injuries (Saber et al, 2017;Scott-Hewitt et al, 2017;Wu et al, 2017), as well as in other axonal injury models (Kobayashi et al, 2016;Tay et al, 2018). Additionally, an increase in sTREM2 could be found at the peak of TREM2 microglial expression after PPT, which was not detected after FNA.…”
Section: Trem2 Is Increased In Activated Microglial Cells After Both supporting
confidence: 91%
“…Certain specificity of TREM2 for phagocytosis of myelin debris and apoptotic neurons has already been suggested based also on TREM2 ligands (Gervois and Lambrichts, 2019). In the case of myelin phagocytosis, similarly to our observations, TREM2 increases its expression correlating to myelin debris appearance in demyelinating models (Piccio et al, 2007;Takahashi et al, 2007;Scott-Hewitt et al, 2017). Overexpression of TREM2 in administered bone-marrow-derived cells improved myelin clearance in EAE-induced mice (Takahashi et al, 2005), while TREM2 blockade increased demyelination (Piccio et al, 2007).…”
Section: Trem2+ Cells Expressed Markers Related To Proliferation and supporting
confidence: 87%
“…We see clear evidence of macrophages in the sciatic nerve at 16 wk, and the reduced debris in the interaxonal space could be from their infiltration and clearance of myelin debris. It has been shown previously that GALC-sufficient macrophages are critical to eliminate myelin debris in an induced model of multiple sclerosis (20). However, we believe that it is unlikely that the infiltration of GALCLAMP1sufficient macrophages alone accounts for the transient improvement in motor function.…”
Section: Discussionmentioning
confidence: 69%
“…Fourteen candidate genes previously associated with MS by GWAS (Beecham et al, 2013; Patsopoulos et al, 2019; Sawcer et al, 2011) were selected based on the accomplishment of one or two of the following criteria: (a) their differential gene expression between MS patients and healthy controls in microarray studies performed by our group in peripheral blood mononuclear cells (PBMC; unpublished data; criterion 1; see Supporting Information Text); (b) their potential contribution to the pathogenesis of MS according to the literature beyond its association with MS risk in the GWAS study (criterion 2). The 14 genes selected for DNA resequencing were the following: Fc receptor like 1 ( FCRL1 ; criterion 2: Comabella et al, 2016), regulator of G protein signaling 1 ( RGS1 ; criterion 1: upregulated in MS patients vs. controls; criterion 2: Tran et al, 2010), translocase of inner mitochondrial membrane domain containing 1 ( TIMMDC1 ; criterion 1: downregulated in MS patients vs. controls), hematopoietically expressed homeobox ( HHEX ; criterion 1: downregulated in MS patients vs. controls ) , C–X–C motif chemokine receptor 5 ( CXCR5 ; criterion 2: Klimatcheva et al, 2015), lymphotoxin beta receptor ( LTBR ; criterion 2: Inoue et al, 2016), Ts translation elongation factor, mitochondrial ( TSFM ; criterion 2: Alcina et al, 2013), galactosylceramidase ( GALC ; criterion 2: Scott‐Hewitt et al, 2017), TNF receptor associated factor 3 ( TRAF3 ; criterion 1: upregulated in MS patients vs. controls), signal transducer and activator of transcription 3 ( STAT3; criterion 2: Benveniste, Liu, McFarland, & Qin, 2014), TNF superfamily member 14 ( TNFSF14 ; criterion 1: downregulated in MS patients vs. controls; criterion 2: Malmeström et al, 2012), IFI30, lysosomal thiol reductase ( IFI30 ; criterion 2: West & Cresswell, 2013), CD40 molecule ( CD40 ; criterion 2: Chen et al, 2016) and cytochrome P450 family 24 subfamily A member 1 ( CYP24A1 ; criterion 2: Ramasamy et al, 2014).…”
Section: Methodsmentioning
confidence: 99%